A New Tool to Assess the Perception of Stretching Intensity. Issue 9 (September 2015) - Freitas, Sandro R.; Vaz, João R.; Gomes, Luis; Silvestre, Rui; Hilário, Edgar; Cordeiro, Nuno; Carnide, Filomena; Pezarat-Correia, Pedro; Mil-homens, Pedro
Abstract : Abstract: Freitas, SR, Vaz, JR, Gomes, L, Silvestre, R, Hilário, E, Cordeiro, N, Carnide, F, Pezarat-Correia, P, and Mil-homens, P. A new tool to assess the perception of stretching intensity. J Strength Cond Res 29(9): 2666–2678, 2015—This study aimed to develop a valid and reliable scale to assess the perception of stretching intensity below and above the maximal range of motion. Experiments were conducted through a passive leg extension angle-torque assessment to healthy population ( n = 90). In the study's first phase, the visual, numerical, and description of the stretching intensity scale (SIS) components were developed. The visual analog scale (VAS) score, absolute magnitude estimation (AME) score, and verbal stretching intensity symptom descriptors were assessed for different stretching intensities. In the second phase, the SIS was tested for validity, reliability, scale production, and estimation properties as well as responsiveness to stretching. In the first phase, a high correlation was found between SIS score and range of motion (ROM), as well as SIS and torque in both submaximal (intraclass correlation coefficient [ICC] = 0.89–0.99, r 2 = 0.88–0.99) and supramaximal (ICC = 0.75–0.86, r 2 = 0.68–0.88) stretching intensities. The AME and VAS scores fitted well in an exponential model for submaximal stretching intensities ( y = 14.829e 0.0187 x, ICC = 0.97 [0.83–0.99], r 2 = 0.98), and in a linear model for supramaximal stretching intensities ( y = 0.7667 x − 25.751, ICC = 0.97 [0.89–0.99], r 2 = 0.9594). For the second phase, a high correlation was found between SIS score and ROM ( r = 0.70–0.76, ICC = 0.76–0.85), as well as SIS and torque ( r = 0.62–0.88, ICC = 0.57–0.85). The interday reliability was high to produce ( r = 0.70, ICC = 0.70 [0.50–0.83]) or estimate ( r = 0.89, ICC = 0.89 [0.82–0.93]) stretching intensities. The acute stretching effects on ROM and passive torque were detectable using the SIS. It is expected a high application in assessing the stretch intensity using the SIS in future studies and practical interventions. Abstract : Supplemental Digital Content is Available in the Text.